Simulation experiences of paramedic students: a cross-cultural examination - Williams B; Abel C; Khasawneh E; Ross L; Levett-Jones T (Advances in Medical Education and Practice, 2016)
Brett Williams,1 Chloe Abel,1 Eihab Khasawneh,2 Linda Ross,1 Tracy Levett-Jones31Department of Community Emergency Health & Paramedic Practice, Monash University, Frankston, Victoria, Australia; 2Faculty of Applied Medical Sciences, Jordan University of Science and Technology, Irbid, Jordan; 3School of Nursing and Midwifery, The University of Newcastle, Callaghan, New South Wales, AustraliaBackground: Simulation-based education is an important part of paramedic education and training. While accessing clinical placements that are adequate in quality and quantity continues to be challenging, simulation is being recognized by paramedic academics as a potential alternative. Examining students’ satisfaction of simulation, particularly cross-culturally is therefore important in providing feedback to academic teaching staff and the international paramedic community.Objective: This study aimed to compare simulation satisfaction among paramedic students from universities in Australia and Jordan.Methods: A cross-sectional study using a paper-based English version of the Satisfaction with Simulation Experience Scale was administered to paramedic students from all year levels.Results: A total of 511 students participated in this study; 306 students (60%) from Australia (Monash University) and 205 students (40%) from Jordan (Jordan University of Science and Technology). There were statistically significant differences with large effect size noted in all three original factors between Australian and Jordanian students: debrief and feedback (mean =38.66 vs mean =34.15; P<0.001; d=0.86), clinical reasoning (mean =21.32 vs mean =18.28; P<0.001; d=0.90), and clinical learning (mean =17.59 vs mean =15.47; P<0.001; d=1.12).Conclusion: This study has demonstrated that simulation education is generally well received by students in Australia and Jordan although Australian students reported having higher satisfaction levels then their Jordanian counterparts. These results provide important data for paramedic educators involved in simulation-based education and training in Australia and Jordan and pave the way for other cross-cultural examinations to be explored.Keywords: allied health worker, culture, paramedics, simulation, undergraduate, student, education